2018
DOI: 10.1038/s41598-018-33075-w
|View full text |Cite
|
Sign up to set email alerts
|

Surface-modified three-dimensional graphene nanosheets as a stationary phase for chromatographic separation of chiral drugs

Abstract: Carbon-based stationary phases for chromatographic separation have been commercially available since the 1980s. Porous graphitic carbon liquid chromatography columns are known to be highly resistant to aggressive mobile phases and extreme pH values of solvents and eluents, an important advantage compared to conventional silica-based alternatives. In our work, we demonstrate a new variant of carbon-based stationary phases for liquid chromatography, specifically developed for chiral separation. Mesoporous three-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…The relatively strong D-line, as well as the presence of spectral background, indicate the rather non-uniform structure of the utilized material. TCNEO-treated graphite demonstrated significant spectral changes, with the appearance of a strong broad-range fluorescent signal, consistent with prior findings 22,23 . Upon reduction, the fluorescence intensity decreased, consistent with the Auger results above.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The relatively strong D-line, as well as the presence of spectral background, indicate the rather non-uniform structure of the utilized material. TCNEO-treated graphite demonstrated significant spectral changes, with the appearance of a strong broad-range fluorescent signal, consistent with prior findings 22,23 . Upon reduction, the fluorescence intensity decreased, consistent with the Auger results above.…”
Section: Resultssupporting
confidence: 89%
“…Upon reduction, the fluorescence intensity decreased, consistent with the Auger results above. The C-N line at around 2230 cm −1 , usually appearing in Raman spectra of TCNEO-modified few-layer graphene or highly uniform graphite, was masked by strong fluorescence signal in our samples 23 . Biotinylation and SPPS induced further changes in the spectra, particularly in the fluorescence component.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Interestingly, computational simulations using density functional theory also showed the applicability of nanoporous graphene, when functionalized by a chiral bouncer molecule [171]. In another exciting work, Candelaria et al [105] demonstrated the fabrication of new type of chemically stable, versatile and cost-effective graphene-based CSPs for enantiomeric separation using LC. The group employed functionalized mesoporous 3D graphene nanosheets for the enantiomeric separation of pharmaceutical grade racemic mixtures of model ibuprofen and thalidomide.…”
Section: Enantiomeric Separation By Chiral Nanoparticlesmentioning
confidence: 99%
“…1 Particularly in pharmaceutical industry, the demand for single enantiomer has keep rising because the pharmacological effect of lots of chiral medicines is restricted to one of the enantiomers. 2,3 People expend so much effort to find more efficient ways of procuring single pure enantiomers to meet the grow demand in pharmaceutical industry. Although enormous steps have been made in asymmetric synthesis, 4 chiral separation is still the most common method of getting single pure enantiomer and plays an important role in the industrial production of enantiomers because of its reliability and applicability in industry.…”
Section: Introductionmentioning
confidence: 99%